Health Care System in Goa: Analysis of Role in Sustainable Development - Ferrao e Fernandes, Anna Rovina (Ushus Journal of Business Management, 2005)
The notion of human well-being includes the crucial attributes of leading a healthy life free from illness and ailments and a reasonable life span. Experience shows that economic prosperity measured in terms of quantitative indicators does not always ensure enrichment in quality of life, but it is reflected in broader dimensions of well-being such as health, which is desirable in sustaining the development process. Hence evaluating the achievements on health front acquires importance. Health policies in developing countries including India have focused on the issues related to population growth, common diseases, nutrition, disabilities, newly emerging diseases such as AIDS, occupational diseases, mental diseases and so on. Along with this earlier health agenda, increasing urbanization has thrown up new health challenges related to environment pollution, increased exposure to toxic substances in everyday life and life styles related health problems. The paper highlights the importance of a well-managed health care system in economic development. It discusses the vital statistics indicating health status of Goa. It analyzes'the trends in health sector expenditure as a proportion of Goa's NSDP. It attempts to examine if the health system in Goa is well-equipped to face the emerging health challenges to ensure sustainable development of the economy.